Influence of the Constitutive Flow Law in FEM Simulation of the Radial Forging Process - Olivier Pantalé; Babacar Gueye (Journal of Engineering)
Radial forging is a widely used forming process for manufacturing hollow products in transport industry. As the deformation of the workpiece, during the process, is a consequence of a large number of high-speed strokes, the Johnson-Cook constitutive law (taking into account the strain rate) seems to be well adapted for representing the material behavior even if the process is performed under cold conditions. But numerous contributions concerning radial forging analysis, in the literature, are based on a simple elastic-plastic formulation. As far as we know, this assumption has yet not been validated for the radial forging process. Because of the importance of the flow law in the effectiveness of the model, our purpose in this paper is to analyze the influence of the use of an elastic-viscoplastic formulation instead of an elastic-plastic one for modeling the cold radial forging process. In this paper we have selected two different laws for the simulations: the Johnson-Cook and the Ludwik ones, and we have compared the results in terms of forging force, product's thickness, strains, stresses, and CPU time. For the presented study we use an AISI 4140 steel, and we denote a fairly good agreement between the results obtained using both laws.